Innovative Strategies For Arabic Language Learning Across Educational Levels: An Analytical Dissertation Study - Abdul Wahab Rosyidi; Umi Machmudah; Khofid Roziki; Abdurrauf; Faisol Mahmud Adam (Al-Muyassar: Journal of Arabic Education, 2026)
Providing fast, accurate, and accessible Arabic language learning in Islamic educational institutions—both formal and informal—is still a challenge. Many teaching strategies rely on limited resources, making Arabic seem hard to learn and lacking professionalism. This study explores the theories used in innovating teaching strategies and evaluates the outcomes of these innovations based on doctoral dissertations for elementary, secondary, and higher education levels. The research uses a qualitative approach with library research methods, focusing on dissertations from the Doctoral Program in Arabic Language Education (2012–2022). The main data include the theories that guided the innovations and the results achieved, while secondary data consist of curricula, syllabi, and teaching modules. Data collection methods include documentation, observation, interviews, and analysis techniques such as data reduction, categorization, triangulation, and drawing conclusions. Findings indicate that innovations in Arabic teaching strategies are built on theories such as Multiple Intelligences, Robert Mill Gagné’s Micro Strategies, Contextual Teaching, Constructivism (PJBL), HOTs, SIOP, and 4Cs. Innovative strategies include: (1) adapting learning objectives to match the applied theories, (2) creating teaching materials aligned with these objectives, (3) combining traditional and modern teaching methods, (4) integrating conventional media with digital platforms, and (5) using diverse evaluation methods, including authentic, portfolio-based, formative, and summative assessments.